2018
DOI: 10.3389/fphar.2018.00469
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic Acid and Progesterone Alone or in Combination Ameliorate Retinal Degeneration in an Experimental Model of Hereditary Retinal Degeneration

Abstract: Retinitis pigmentosa (RP) is a group of inherited retinopathies characterized by photoreceptors death. Our group has shown the positive progesterone (P4) actions on cell death progression in an experimental model of RP. In an effort to enhance the beneficial effects of P4, the aim of this study was to combine P4 treatment with an antioxidant [lipoic acid (LA)] in the rd1 mice. rd1 and control mice were treated with 100 mg/kg body weight of P4, LA, or a combination of both on postnatal day 7 (PN7), 9, and 11, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Genetic material can be potentially incorporated to the retina and eventually restore the visual functionality in the zone in which it is injected but, without a global actuation on the whole retina by maintaining the health of the adjacent cells, an inflamed surrounding could end in a complete failure of any therapy. Hence, the concomitant use of antiinflammatory, antioxidant and antiapoptotic agents, as well as neurotrophic and growth factors, will provide an adequate environment of healthy cells that will help to achieve a sustained functional restoration of the visual function (Figure 1), as it has been shown for the combination of progesterone and lipoic acid in a mouse model of RP (Ramirez-Lamelas et al, 2018).…”
Section: Current and Future Therapeutic Strategies For The Treatment Of Retinal Neurodegenerative Diseasesmentioning
confidence: 98%
“…Genetic material can be potentially incorporated to the retina and eventually restore the visual functionality in the zone in which it is injected but, without a global actuation on the whole retina by maintaining the health of the adjacent cells, an inflamed surrounding could end in a complete failure of any therapy. Hence, the concomitant use of antiinflammatory, antioxidant and antiapoptotic agents, as well as neurotrophic and growth factors, will provide an adequate environment of healthy cells that will help to achieve a sustained functional restoration of the visual function (Figure 1), as it has been shown for the combination of progesterone and lipoic acid in a mouse model of RP (Ramirez-Lamelas et al, 2018).…”
Section: Current and Future Therapeutic Strategies For The Treatment Of Retinal Neurodegenerative Diseasesmentioning
confidence: 98%
“…RP has been related to oxidative stress [48,49,50,51,52], not only while rods die but also when cones are secondarily dying. Rods degeneration decreases oxygen consumption in the retina, inducing a large excess of oxygen in the outer retina [53].…”
Section: Retinitis Pigmentosamentioning
confidence: 99%
“…This GSH effect has been demonstrated through experiments with buthionine sulfoximine treatment (an inhibitor of γ-glutamylcysteine synthetase, the enzyme that controls the GSH synthesis) [1]. When LA is administered in combination with progesterone in rd1 mice, Ramirez-Lamelas et al, [5] have demonstrated a decrease in photoreceptors death, and in the GFAP staining; the overexpression of GFAP can be used as an indicator of stress and retinal damage, as well as the activation of Müller cells in rd1 mice retinas [5]. These results highlight that progesterone and LA administered in combination have better results than when administered separately [5].…”
Section: Lipoic Acid: An Antioxidant and Anti-inflammatory Moleculementioning
confidence: 99%
“…When LA is administered in combination with progesterone in rd1 mice, Ramirez-Lamelas et al, [5] have demonstrated a decrease in photoreceptors death, and in the GFAP staining; the overexpression of GFAP can be used as an indicator of stress and retinal damage, as well as the activation of Müller cells in rd1 mice retinas [5]. These results highlight that progesterone and LA administered in combination have better results than when administered separately [5]. To more details about the treatments, please see Table 2.…”
Section: Lipoic Acid: An Antioxidant and Anti-inflammatory Moleculementioning
confidence: 99%
See 1 more Smart Citation